PENGARUH KOMPETENSI, KECERDASAN EMOSIONAL DAN EFIKASI DIRI TERHADAP KENYAMANAN PIMPINAN DALAM MELAKUKAN PENILAIAN KINERJA KARYAWAN - Didik Purwanto, Ernawati (Universitas Slamet Riyadi, 2010)
ABSTRACT Result of the research indicate that increase of self awareness cause the head freshment comfort in performance assessment of employees PD. BPR Bank Daerah Kabupaten Karanganyar will be downhill progressively, excelsior of emotional resilience cause of the head freshment comfort in performance assessment of employees PD. BPR Bank Daerah Kabupaten Karanganyar will progressively mount, excelsior of motivate cause of the head freshment comfort in performance assessment of employees PD. BPR Bank Daerah Kabupaten Karanganyar will progressively mount, self efficacy excelsior cause of the head freshment comfort in performance assessment of employees PD. BPR Bank Daerah Kabupaten Karanganyar will progressively mount.This research conclude that self efficacy represent most dominant variable have an effect on to head freshment comfort in performance assessment of employees PD. BPR Bank Daerah Kabupaten Karanganyar , this matter can be seen from most dominant beta coefficient value is self efficacy variable posed at with beta coefficient value equal to 0,567. Self efficacy have dominant or highest coefficient can be interpreted that the variable have most dominant role to strive the make-up of head freshment comfort in performance assessment of employees PD. BPR Bank Daerah Kabupaten Karanganyar. Keywords: Self awareness, emotional intellegence, motivation, self efficacy and head freshment comfort in performance assessment of employees.